Математичні основи управління режимами енергетичних систем - Кисленко, Д. Ю.; Тарасова, В. В. (НТУ "ХПІ", 2012)
У статі розглянуті деякі аспекти методів управління режимами енергетичних систем, розглянуті математичні методи аналізу статичної стійкості, приділено увагу теорії стійкості по А. М. Ляпунову

In fl oors considered some aspects of methods of management of the power systems the modes, the mathematical methods of analysis of static fi rmness are considered, attention of theory of firmness is spared for And. M. of Lyapunovu
Аnaliz of methods of management the modes of the power systems
Keywords: методи повної інтеграції; методи неповної інтеграції; методи квазіінтеграцїї; диференціальні методи; баланс активної та реактивної потужності; метод А. М. Ляпунова; статична стійкість; номінальний режим; methods of complete integration; methods of incomplete integration; methods of kvaziintegracii; differential methods; balance of active and reactive power